The Impact of Exposure to Traumatic Narrative: The Lived Experience of Malaysian Counsellors - Nur Husna Mohd. Hafiz; Mohd Zaliridzal Zakaria; Wan Mohd Fazrul Azdi Wan Razali; Nurhafizah Mohd. Sukor; Marina Munira Abdul Mutalib; Mohamed Fauzi Othman (USIM Press, 2024)
E-Proceeding Islamic Science Social Postgraduate Conference 2023 (ISSPeC 2023) “The Tradition of Knowledge as a Catalyst for the Sustainability of Civilization”/ editors : Anita Binti Ismail, Farah Laili Binti Muda @ Ismail, Kamal Azmi Bin Abd Rahman, Afi Roshezry Bin Abu Bakar, Ikmal Hafiz Bin Jamal Organized by: Institut Sains Islam (ISI) & Pusat Pengajian Teras (PPT) 30 November 2023